Perancangan game attahdiid: Bertahan hidup dalam pondok dengan metode finite state machine - Zaidan, Muchammad Alif; Nugroho, Fresy; Karami, Ahmad Fahmi; Pradana, Reza Putra (Maliki Interdisciplinary Journal, 2024)
This research discusses the design and development of the game "Attahdiid: Survival in the Hut," a first-person horror survival game that utilizes the Finite State Machine (FSM) method and Maze Generation algorithm. FSM is employed to control character behavior, organize the storyline, and create challenges within the game. The Maze Generation algorithm enhances efficiency in automatically creating game levels, resulting in a dynamic and varied gaming experience. The game creates an authentic atmosphere of a pesantren hut through meticulously considered character and item designs. The implementation of a simple menu structure facilitates game settings, improves player accessibility, and emphasizes the gaming experience. Beyond providing entertainment, "Attahdiid" integrates religious values and complex challenges, immersing players in a deeper experience. By combining creativity in game design with technological implementation, "Attahdiid" is not only an engaging game but also reflects a holistic approach to game development that can serve as inspiration for developers and researchers in the future.